Stimulating Children's Fine Motor Development: Analysis of the Effect of Using Magic Straw Media - Nelviyanti Nelviyanti; Dewi Sri Suryanti (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2025)
This research aims to determine the effect of using magic straws on the fine motor development of children aged 5-6 years at Al-Muhsinin Kindergarten, Sungai Aur District, West Pasaman Regency, West Sumatra Province. This research uses a quantitative research approach with experimental research methods and uses a pre-experimental type with a one group pretest-posttest research design. The research subjects were teachers and children, while the object was the influence of using magic straws on the fine motor development of children aged 5-6 years at Al-Muhsinin Kindergarten. The population of this study was all children at Al-Muhsinin Kindergarten, totaling 25 children and the sample for this research was children aged 5-6 years, totaling 17 children, using the Purposive Sampling technique. Data collection techniques are observation, tests and documentation. The data analysis technique uses statistical analysis with a t-test using a formula using the SPSS version 29 program. The statistical t test results have a sig value. 0.001 < 0.05 with tcount = 32.168 > ttable = 1.753. So Ho is rejected and Ha is accepted, so it can be concluded that there is an influence of the use of magic straws on the fine motor development of children aged 5-6 years in Al-Muhsinin Kindergarten, Sungai Aur District, West Pasaman Regency, West Sumatra Province, namely 79.66 %.Keywords: Magic Straws; Fine Motor Skills; Early ChildhoodAbstrak. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media sedotan ajaib (magic straws) terhadap perkembangan motorik halus anak usia 5-6 tahun di TK Al-Muhsinin Kecamatan Sungai Aur Kabupaten Pasaman Barat Provinsi Sumatera Barat. Penelitian ini menggunakan pendekatan penelitian kuantitatif dengan metode penelitian eksperimen dan menggunakan jenis pre-eksperimental dengan desain penelitian one group pretest-posttest. Subjek penelitian adalah guru dan anak, sedangkan objeknya yaitu pengaruh penggunaan media sedotan ajaib (magic straws) terhadap perkembangan motorik halus anak usia 5-6 tahun di TK Al-Muhsinin. Populasi penelitian ini adalah seluruh anak di TK Al-Muhsinin yang berjumlah 25 anak dan sampel penelitian ini adalah anak usia 5-6 tahun yang berjumlah 17 anak, dengan menggunakan teknik Purposive Sampling. Teknik pengumpulan data yaitu observasi, tes, dan dokumentasi. Teknik analisis data menggunakan analisis statistik dengan uji t-test menggunakan rumus dengan menggunakan program SPSS versi 29. Hasil uji t statistik  nilai sig. 0,001 < 0,05 dengan  thitung  = 32,168 > ttabel = 1,753. Maka Ho ditolak dan Ha diterima, sehingga dapat disimpulkan bahwa terdapat pengaruh penggunaan media sedotan ajaib (magic straws) terhadap perkembangan motorik halus anak usia 5-6 tahun di TK Al-Muhsinin Kecamatan Sungai Aur Kabupaten Pasaman Barat Provinsi Sumatera Barat yaitu sebesar 79,66%.Kata kunci: Sedotan Ajaib (Magic Sraws); Motorik Halus; Anak Usia Dini